2008
DOI: 10.1007/s10096-008-0504-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bactibilia on the course and outcome of laparoscopic cholecystectomy

Abstract: Although bactibilia is an important condition of acute cholecystitis, its effect on the course and outcome of the infectious gallbladder disease has rarely been studied, particularly in relation to the laparoscopic procedure. The current study attempts to learn more about the inter-relationship between bactibilia and laparoscopic cholecystectomy during acute cholecystitis. Demographic, preoperative, operative, and postoperative data were prospectively collected in every patient with acute cholecystitis treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
42
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 10 publications
10
42
1
1
Order By: Relevance
“…This is consistent with other studies and is thought to be caused by age-dependent physiological changes (decreased biliary motility and clearance, increasing duodenal motor disorders and anatomical/functional alterations, diabetes mellitus) [9,11,12,13]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with other studies and is thought to be caused by age-dependent physiological changes (decreased biliary motility and clearance, increasing duodenal motor disorders and anatomical/functional alterations, diabetes mellitus) [9,11,12,13]. …”
Section: Discussionsupporting
confidence: 92%
“…Nor did patients with bactobilia have more infectious complications. This is in contrast with two other studies on the effect of bile cultures on the outcome of LC [11,12]. In the study by Morris-Stiff et al [12] more infectious complications occurred in the group with positive bile cultures (p < 0.05).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In some studies, bactobilia has been shown to be a risk factor predisposing to postoperative infectious complications, which are one of the most important concerns of surgeons, especially in laparoscopic surgery (4,5). The rate of post-operative wound infection after elective cholecystectomy in uncomplicated symptomatic gallstone ranges from 2.3% to 20% (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining bile culture during biliary surgery is mainly advised only in patients with some predisposing factors that could increase the risk of such infections. These risk factors include pyrexia, previous biliary instrumentation, previous biliary sepsis, bilioenteric anastomosis, immune suppression status, a palpable gallbladder, elevated WBC count, and elevated serum levels of alkaline phosphatase and old age (2,5,8,10,11). However, reports are still conflicting over the use of bile culture at biliary surgery (6,12).…”
Section: Introductionmentioning
confidence: 99%